The Influence of Service Quality, Facilities and Information Technology on Consumer Satisfaction in Radiology Haji Hospital Surabaya - Nawiri, Adib Rosyad; Handoko, Yunus; Kusdyah, Ike (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze the effect of service quality, facilities, and information technology on consumer satisfaction at the Diagnostic and Interventional Radiology Installation of the Haji Regional General Hospital (RSUD) Surabaya, East Java. The method used in this study was non-probability sampling, involving 77 respondents who were consumers who had undergone examinations at the radiology installation. Data analysis was carried out using Smart PLS 4. The results of the study showed that partially, service quality (X1) had a significant effect on consumer satisfaction. Conversely, facilities (X2) and information technology (X3) did not show a significant effect on consumer satisfaction. However, simultaneously, the three variables—service quality, facilities, and information technology—had a significant effect on consumer satisfaction (Y). This finding emphasizes the importance of developing optimal facilities and implementing information technology to improve consumer satisfaction in radiology services.